Annual Plan 1995-96 Volume-X X. Education. Sports. Arts and Culture. Hill Areas Government of Assam - Planning Commission (Planning Commission, 1995)
Karbi Anglong District and North Cachar Hill District constituted the sixth schedule Part-I areas of Assam. the State's peculiar geographical and to poor graphical position with multi-lingua franca and population have always stood in the way for speedy development of education and this more apparent in case of the two hill district of Assam. the total population of the two hill districts as per 1991 census is about 8 lakhs.
Government of Assam, Development Commissioner For Hill Areas